2021
DOI: 10.1007/s41133-021-00050-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress among School Students in Distance Learning During the COVID-19 Pandemic in the Gaza Strip, Palestine

Abstract: The rapid outbreak of COVID-19 is a global health problem that has a significant effect on the educational systems. Therefore, students shifted to distance learning through the digital platform. Since COVID-19 has consequences on mental health, the present study examined the perceived stress level in school students in distance learning during the COVID-19 period. A cross-sectional study of a sample consisting of 385 school students evaluated the Perceived Stress Scale (PSS) and their concerns and emotions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Radwan et al studied the perceived stress level in distance learning students during the COVID-19 period and found that female students had remarkably higher perceived stress levels compared to male students. They also had a greater chance of having moderate stress compared to males (Radwan et al ., 2021). On the other hand, stress is an important factor affecting OCD and may act as both a triggering and aggravating factor (Raposo-Lima & Morgado, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Radwan et al studied the perceived stress level in distance learning students during the COVID-19 period and found that female students had remarkably higher perceived stress levels compared to male students. They also had a greater chance of having moderate stress compared to males (Radwan et al ., 2021). On the other hand, stress is an important factor affecting OCD and may act as both a triggering and aggravating factor (Raposo-Lima & Morgado, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The findings were consistent with DiPietro et al [ 18 ] who reported that students spent less time on learning. The students were bound to their homes, leading to stress and anxiety which negatively affected the ability of students to complete assignments and perform academic activities [ 24 , 55 57 ]. This led to the Asian Development Bank [ 20 ] and Fitzpatrick et al [ 24 ] stating that learning loss was related to the physical skills, social skills, emotional skills, mental health, and well-being of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Students' learning at home cannot be controlled due to factors such as parents' work or lack of sufficient knowledge (Azubuike et al, 2021). There are studies (Husky et al, 2020;Radwan et al, 2021) on when students' stress levels decrease during the pandemic period. Excessive stress and excitement are factors that prevent learning (Kurniawan & Budiyono, 2021;Rai et al, 2021).…”
Section: Discussionmentioning
confidence: 99%